2006
DOI: 10.1021/np0505061
|View full text |Cite
|
Sign up to set email alerts
|

Bisabolane Sesquiterpenes from the Roots of Ligularia cymbulifera

Abstract: Eight new highly oxygenated bisabolane sesquiterpenes (1-8), of which one contains a chlorine atom, were obtained in a phytochemical investigation of the roots of Ligularia cymbulifera, and their structures were elucidated by interpretation of spectroscopic data. Their relative configurations were clarified by a detailed analysis of (1)H NMR coupling constants and by NOE experiments. Compounds 1-8 were evaluated for antimicrobial activity against three bacterial cultures and a yeast culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 11 publications
2
20
0
Order By: Relevance
“…The EI-MS of 2 gave a molecular ion peak at m/z = 548, accompanied by an isotopic peak at m/z = 550 (their relative abundance ratio was 3 : 1), suggesting the presence of a chlorine atom [41], which was further supported by the fragment at m/ group at δ = 166.2 (C-1 ′ ) suggested that the angeloyl group was attached to C-6.…”
Section: Resultsmentioning
confidence: 93%
“…The EI-MS of 2 gave a molecular ion peak at m/z = 548, accompanied by an isotopic peak at m/z = 550 (their relative abundance ratio was 3 : 1), suggesting the presence of a chlorine atom [41], which was further supported by the fragment at m/ group at δ = 166.2 (C-1 ′ ) suggested that the angeloyl group was attached to C-6.…”
Section: Resultsmentioning
confidence: 93%
“…Hydrogen atoms were fixed at calculated positions and refined using a riding mode. The absolute configuration was assigned on the basis of the absolute structure parameter, which refined to a value of −0.11 (3). The final indices were R = 0.0295, R w = 0.0809 with goodness-of-fit = 1.031.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The IR absorption at 1750 cm −1 represented the characteristic band of a δ-lactone moiety. In addition, in its NMR spectra, one carboxylic methyl ester group at δ H 3.81 (s, OCH 3 ) and δ C 53.0 (OCH 3 ), 172.5 (C-1) was observed. Its 1 H NMR spectrum indicated the presence of one tertiary methyl at δ 1.59 (s, H 3 -7), two secondary methyls at δ 1.16 (d, J = 7.2 Hz, H 3 -8) and 1.44 (d, J = 5.4 Hz, H 3 -10), one methylene at δ 2.11 (dd, J = 14.7, 6.6 Hz, H-4α) and 1.87 (dd, J = 14.7, 3.9 Hz, H-4β), and two methines at δ 2.57 (m, H-3) and 3.03 (q, J = 5.4 Hz, H-9).…”
mentioning
confidence: 99%
“…77 Eight new bisabolane sesquiterpenes 73-80 have been isolated from the roots of Ligularia cymbulifera. 78 Another compound of this type 81 has been found in an extract from Achillea clavennae. 79 The aerial parts of Lippia dulcis 80 contain six novel bisabolane sesquiterpenes, which have been named peroxylippidulcines A-C 82-84, peroxyepilippidulcine B 85, epilippidulcine B 86 and epilippidulcine C 87.…”
Section: Bicyclofarnesanementioning
confidence: 99%